Probiotic characterization of Limosilactobacillus reuteri strain isolated from cow’s milk - Divya SB; Radhai Sri S (South Eastern European Journal of Public Health, 2025)
Lactic acid bacteria (LAB) are commonly found in milk and dairy products, and their probiotic characteristics make them valuable for use in food products. Understanding the antibiotic susceptibility of LAB is crucial to ensure the safe use of LAB-based products. This study investigated the probiotic characteristics including tolerance to pH, bile salts , antibiotic susceptibility and antibacterial activity of a strain isolated from raw cow’s milk. Pure colonies were identified by 16S rRNA gene sequencing as Limosilactobacillus reuteri. The antibacterial activities of an overnight culture of Lactobacillus reuteri against four test microorganisms: Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus were studied using the agar well diffusion method. Antibiotic susceptibility profile of the isolated strain were tested using disc diffusion method for ciprofloxacin(8mcg), ceftazidime(10mcg), ampicillin(10mcg), penicillin(10mcg), amoxiclav(10mcg), vancomycin (30mcg), amikacin(10mcg), methicillin(5mcg), chloramphenicol(30mcg) and cefozolin(30mcg). The results indicated that L. reuteri isolated from cow’s milk was tolerant to acidic conditions and bile salts and demonstrated significant antimicrobial activity against the test microorganisms, suggesting its potential use as a natural antibacterial agent. Additionally, the strain exhibited resistance to the antibiotics tested, highlighting its safety profile. These findings suggested that the isolated LAB strain has beneficial properties and would serve as a starter culture for safe use in commercial food products.